2011
DOI: 10.1371/journal.pone.0021152
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Classical Hodgkin Lymphoma and Its Association with Epstein Barr Virus in Northern China

Abstract: BackgroundThe incidence of classical Hodgkin lymphoma (cHL) and its association with Epstein-Barr virus (EBV) varies significantly with age, sex, ethnicity and geographic location. This is the first report on epidemiological features of cHL patients from Northern regions of China. These features are compared to data from a previously published Dutch cHL population.Methodology/Principal Findings157 cHL patients diagnosed between 1997 and 2008 in the North of China were included after histopathological re-evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 29 publications
5
20
1
Order By: Relevance
“…There were 111(35%) cases of lymphomas (Abuidris et al, 2008). Such findings were previously reported (Huang et al, 2011).…”
Section: Discussionsupporting
confidence: 76%
“…There were 111(35%) cases of lymphomas (Abuidris et al, 2008). Such findings were previously reported (Huang et al, 2011).…”
Section: Discussionsupporting
confidence: 76%
“…This finding is in agreement with some previous studies (Gualco et al, 2010;Dinesh et al, 2011;Huang et al, 2011).…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, the most frequent histological subtype was mixed cellularity (MC). This finding is in accordance to other studies (Araujo et al, 2006;Huang et al, 2011). In general, it is demonstrated that the MC is the most prevalent subtype of HL in underdeveloped countries (Sandoval et al, 2002;Schwartz, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…EBV positive rate of MC in developing country was 70%-90%, followed by NS type (Dinand et al, 2006;Huang et al, 2011). However, in this research, the difference of EBV-DNA load between this two tissue types and other types was not significant (P>0.05).…”
Section: Discussioncontrasting
confidence: 51%